Consideration on the borders of the typical fraud . The problem of fraud law in the crime of tax fraud (2013)
The text addresses the problem of the limits of the relevant criminal conduct in the tax fraud, in particular in relation to the tax avoidance. Also discusses how has faced the problem of tax avoidance, from the perspective by the legal doctrine and the S